Síntese, caracterização e estudo da atividade antitumoral de complexos de paládio(II) com ligantes sulfurados e trifenilfosfina - Rocha, Fillipe Vieira [UNESP] (2013)
In the last years the interest in obtaining new metal drugs has increased considerably. Since the discovery of the antitumor activity of cisplatin in the 60's, many Pt(II) complexes were synthesized, but only few reached the clinical trials. For this reason, the Pd(II) ion has been used systematically in the design of new biologically active compounds. Palladium complexes display the same electron configuration and square planar geometry of platinum compounds, furthermore these complexes can interact through different way towards pharmacological targets. In this work new palladium(II) complexes of the type [PdX2(TA)(PPh3)] and [PdX(L)(PPh3)]X [X = Cl-, Br-, I-, SCN-; TAA = thioacetamide , L = 4-methyl-3-thiosemicarbazide (4-MeT) or 4-phenyl-3-thiosemicarbazide (4-PhT)], were synthesized and characterized. All the compounds were characterized by infrared, nuclear magnetic resonance spectroscopy, elemental analysis and thermogravimetric analysis. The structures of three complexes [(PdI(4-MeT)(PPh3)]I, [Pd(SCN)(4-MeT)(PPh3)](SCN) and [(PdI(4-PhT)(PPh3)]I were determined by single crystal X-ray diffraction and was observerd a square planar environment around the metal center, with the coordination sites occupied by triphenylphosphine, the N,S-donors ligand and iodine atom or thiocyanate group. The in vitro cytotoxicity of the complexes were evaluated against the murine tumor cells LM3 (breast adenocarcinoma) and LP07 (lung adenocarcinoma). The most promising compounds were further evaluated by their ability to interact with a purine base and the DNA. The results showed that DNA is not the primary target of these compounds because they only interacted with this biomolecule at high concentrations. Thus, others potential targets were investigated . The capacity of the complexes to inhibit topoisomerase enzymes was evaluated by electrophoresis, and the data showed that almost all the compounds inhibit this enzyme at a concentration rage...